Relationship between direct and indirect methods for determination of anaerobic running speed - Pereira Guimarães, M.; Almeida Costa Campos, Y.; Santos Almeida, P. A.; Dominguez, R.; Azambuja Pussieldi, G.; Fernandes da Silva, S. (International Journal of Applied Exercise Physiology, 2018)
The present study aims to correlate and verify the agreement of two methods for determination of anaerobic threshold velocity (AnTV): 1) the variable lactate concentration (DMAX); 2) the individual anaerobic threshold (IAT); and 3) an indirect critical velocity test (VCrit) through two distances, all of which were performed on a running track. Seventeen amateur runners participated in the study, performing three procedures for the determination of AnTV and Vcrit. A progressive testing of 6 x 1000 m in running track was performed in order to determine the AnTV and three tests with the distances of 1500 m, 3000 m, and 5000 m were performed in order to determine the VCrit. For the determination of AnTV, the behavior of blood lactate concentrations was used through two identification methods, IAT and DMAX. Bland-Altman`s visual analysis was used to verify agreement and Pearson`s test was used to identify the correlation. It was possible to identify positive correlations between the invasive and non-invasive methods used in the study, and the same was identified in the Bland-Altman`s visual analysis. The study found that the anaerobic threshold velocities in the methods that used blood lactate with the indirect methods (Vcrit) are concordant among them, so the presented methods are safe for the training prescription considering the running speed in the anaerobic threshold (AnT) in runners moderately trained.